Evaluation of Students' Consumption of Beer in Higher Institutions of Learning in Nigeria: Propelling Factors for Choice - Abugu, James O.; Iheanacho, Albert O.; Igwe, Anthony (Journal of Reviews on Global Economics, 2019)
The several brands of beer in Nigeria, with brand extensions, provide the opportunity for consumers to have more options to choose their brands from, and the brewing companies contend with how to make their products the preferred choice among consuming public. Although empirical studies in institutions of higher learning in Nigeria report that some factors influence the choice of beer brand in different places, there is, however, a paucity of information on the propelling factors for choice of beer brand. It is against this backdrop that this study appraised the choice of beer brand in the Nigerian higher institutions. A total number of 166 undergraduate and postgraduate students studying at the Enugu Campus of the University of Nigeria, Nsukka, participated in this study. The study adopted survey design, questionnaire was used and consent was obtained from all the participants before carrying out the study. Questions posed to them were whether social group, price and emotion significantly determine their choice of brand of beer. The result indicated that social group has the greatest percentage of significance propelling factor of 78.9% (agreed and strongly agreed); then emotion, 74.1% (agreed and strongly agreed) and the price of beer 53% (agreed and strongly agreed) which is also significant. Students' social group, emotion and price of beer showed statistical significance when compared in relation to choice of beer. Therefore, students always align with the type of products (beer inclusive) consumed by their social group that has moderate price and emotional appeals when making choice.